PENGEMBANGAN SELF HELP BOOK UNTUK PEMAHAMAN SISWA TENTANG PROKRASTINASI AKADEMIK - Nurfadilah Dilah; Rochani; Raudah Zaimah Dalimunthe (LPPM Universitas Cipta Mandiri, 2024)
One effort to provide students with an understanding of academic procrastination is by developing innovative, effective and efficient information media. This research aims to develop an information media, namely an e-book with the title